Neuro-Ophthalmologic MRI Findings in the Detection of Rhinorrhoea Aetiology. (4th July 2019) - Peker, Elif; Kuru Öz, Diğdem; Kul, Melahat; Erdoğan, Mustafa; Öztuna, Derya; Erden, Memet İlhan
ABSTRACT: The purpose of this study is to evaluate the importance of neuro-ophthalmological magnetic resonance imaging (MRI) findings in the identification of the aetiology of rhinorrhoea, and the differentiation of spontaneous rhinorrhoea from non-spontaneous rhinorrhoea. MR images of 25 patients with spontaneous and 21 patients with non-spontaneous rhinorrhoea were evaluated for the presence of neuro-ophthalmological findings of intracranial hypertension (IHT). These include optic nerve vertical tortuosity, optic nerve sheath enlargement, flattening of the posterior sclera and optic nerve protrusion, as well as other MRI findings of ICH, such as partial empty sella, dilatation of Meckel's cave and the presence of arachnoid pits. IHT findings were more common in the spontaneous group. Six criteria (optic nerve distention, optic nerve vertical tortuosity, posterior flattening of the sclera, partial empty sella, Meckel's cave dilatation and presence of arachnoid pits) differentiate between patient and control groups. Patients with spontaneous cerebrospinal fluid (CSF) leaks should be evaluated for signs of IHT on MRI, as they are present in the majority of spontaneous CSF leaks and are representative of increased intracranial pressure.